PELATIHAN PENGGUNAAN SISTEM INFORMASI DESA KEPADA APARATUR DESA LUMBAN PEA TIMUR - Hutapea, Marlyna Infryanty; Purba, Eviyanti Novita; Perangin-angin, Resianta; Jamaluddin, Jamaluddin; Nainggolan, Rena; Simamora, Roni J.; Saragih, Rijois I. E.; Harianja, Eva J. G.; Lumbantoruan, Gortap; Siringoringo, Rimbun; Sembiring, Rasmulia; Simanjuntak, Stevani L. Z.; Napitupulu, Thomson Januari (Universitas Methodist Indonesia, 2023)
Lumban Pea Timur is one of the villages in Balige District, Toba Samosir Regency, North Sumatra Province. Village development is currently inseparable from the support of information technology, almost every village requires information technology to improve services to the community. The process of conveying information by the village to the resident, namely from the sub-district head to the village head reaches the resident. Processes like this often lead to inaccurate information. All existing regional potentials must be disseminated to show their superiority. Each district has an area called a sub-district and village. The rapid development of the world of communication technology has had a tremendous impact on the pattern of people’s lives. Information systems have made people’s lives dynamic and fast. With the facilities provided, encourages people to take advantage of information and communication technology to assist in their daily activities. The village government of Lumban Pea does not yet have a website address. This has resulted in information owned by the village that cannot be accessed by the wider community, causing this village to be very left behind. In this increasingly advanced technological era, a website-based information system can be implemented in East Lumban Pea village to overcome the above constraints. With the existence of a village information system, the community can directly access the various kinds of information presented. Likewise, village leaders can directly provide or update information related to the village they are fostering. All forms of information regarding population management can be accessed on the village information system page.